SOCIAL CAPITAL AND PERFORMANCE OF SMALL BUSINESS IN MALAYSIA - Nor Hasni Haron (International Journal of Accounting, Finance and Business, 2020)
Globalization, financial and economic development and crisis have contributed some pressure to the growth and survival of small companies. To be competitive in the global as well as national economic, the performance of small business is very essential. However, they are reported to face many problems and many have bankrupt or failed. Applying Resource-based Theory, intangible resources are expected to 1 performance of small businesses. Thus, this study examines the supplier and customer trust relationships as social capital on performance of small businesses. The samples of small-sized manufacturers are taken from Malaysian SMEs 2010 Directory using stratified random sampling. A total of 215 questionnaires that answered by owner-managers is analyzed. The result has shown that buyer-supplier trust has shown a positive significant influence on non-financial performance. On the other hand, buyer-seller trust has no significant influence on non-financial performance of small businesses.